Insights into pH‐induced metabolic switch by flux balance analysis. (30th January 2015) - Ivarsson, Marija; Noh, Heeju; Morbidelli, Massimo; Soos, Miroslav
<x xml:space="preserve">Abstract</x> Lactate accumulation in mammalian cell culture is known to impede cellular growth and productivity. The control of lactate formation and consumption in a hybridoma cell line was achieved by pH alteration during the early exponential growth phase. In particular, lactate consumption was induced even at high glucose concentrations at pH 6.8, whereas highly increased production of lactate was obtained at pH 7.8. Consequently, constraint‐based metabolic flux analysis was used to examine pH‐induced metabolic states in the same growth state. We demonstrated that lactate influx at pH 6.8 led cells to maintain high fluxes in the TCA cycle and malate‐aspartate shuttle resulting in a high ATP production rate. In contrast, under increased pH conditions, less ATP was generated and different ATP sources were utilized. Gene expression analysis led to the conclusion that lactate formation at high pH was enabled by gluconeogenic pathways in addition to facilitated glucose uptake. The obtained results provide new insights into the influence of pH on cellular metabolism, and are of importance when considering pH heterogeneities typically present in large scale industrial bioreactors. © 2015 American Institute of Chemical Engineers Biotechnol. Prog., 31:347–357, 2015